Revealing a word superiority effect using a unique variant of the Latin alphabet: the evidence from Turkish - Jordan, Timothy R.; Kalan, Aleynanur (Frontiers in Psychology, 2024)
When visual stimuli are presented briefly, words are perceived better than nonwords. It is widely accepted that this word superiority effect reflects the efficiency with which words are perceived. However, most of what is known about the effect comes from languages (like English) using the basic Latin alphabet and little is known about whether languages using an alphabetic variant with very different properties can also produce word superiority. Here we report an experiment in which words and nonwords were presented briefly in Turkish, which uses a unique variant of the Latin alphabet containing 29 separate letters, 12 of which are close visual replications of other letters. Despite the potential for visual confusability and perceptual uncertainty, the findings revealed a clear advantage for words over nonwords, indicating that word superiority observed previously for the Latin alphabet can also be observed with the very different variant of this alphabet used for Turkish. Implications of these findings for processes involved in visual word perception are discussed.